Resolvin D2 Reduces UVB Skin Pathology by Targeting Cytokines, Oxidative Stress, and NF-κB Activation - Ingrid C. Pinto; Priscila Saito; Camilla C. A. Rodrigues; Renata M. Martinez; Cristina P. B. Melo; Maiara Piva; Clovis M. Kumagai; David L. Vale; Telma Saraiva-Santos; Allan J. C. Bussmann; Marcela M. Baracat; Sandra R. Georgetti; et al. (Antioxidants)
UVB skin pathology is initiated by reactive oxygen species (ROS), differentiating this condition from other inflammatory diseases involving first the immune cell activation by danger or pathogen molecular patterns followed by oxidative stress. Resolvin D2 (RvD2) has been found to reduce inflammation in preclinical models. However, whether or not RvD2 reduces skin pathology caused by UVB irradiation is not yet known. Therefore, the efficacy of RvD2 on skin pathology triggered by UVB irradiation in female hairless mice was assessed. RvD2 (0.3, 1 or 3 ng/mouse, i.p.) was found to protect the skin against UVB inflammation, as observed in the reduction in edema (46%), myeloperoxidase activity (77%), metalloproteinase-9 activity (39%), recruitment of neutrophils/macrophages (lysozyme+ cells, 76%) and mast cells (106%), epidermal thickening (93%), sunburn cell formation (68%), collagen fiber breakdown (55%), and production of cytokines such as TNF-α (100%). Considering the relevance of oxidative stress to UVB irradiation skin pathologies, an important observation was that the skin antioxidant capacity was recovered by RvD2 according to the results that show the ferric reducing antioxidant power (68%), cationic radical scavenges (93%), catalase activity (74%), and the levels of reduced glutathione (48%). Oxidative damage was also attenuated, as observed in the reduction in superoxide anion production (69%) and lipid hydroperoxides (71%). The RvD2 mechanism involved the inhibition of NF-κB activation, as observed in the diminished degradation of IκBα (48%) coupled with a reduction in its downstream targets that are involved in inflammation and oxidative stress, such as COX-2 (66%) and gp91phox (77%) mRNA expression. In conclusion, RvD2 mitigates the inflammatory and oxidative pathologic skin aggression that is triggered by UVB.